1985
DOI: 10.1111/j.1469-8137.1985.tb03651.x
|View full text |Cite
|
Sign up to set email alerts
|

ACTIVITY OF GLUTAMINE SYNTHETASE AND GLUTAMATE DEHYDROGENASE IN TRIFOLIUM SUBTERRANEUM L. AND ALLIUM CEPA L: EFFECTS OF MYCORRHIZAL INFECTION AND PHOSPHATE NUTRITION

Abstract: Summary Activities of glutamate dehydrogenase and glutamine synthetase were determined using crude extracts of roots and shoots of mycorrhizal and non‐mycorrhizal plants of Trifolium subterraneum L. and Allium cepa L., grown at different levels of fertilizer phosphate. Glutamate dehydrogenase activity was low in all tissues [0.1 to 1.6 μmol NAD(P)H oxidized min−1 gFW−1 tissue] and there was no consistent effect of mycorrhizal infection or phosphate nutrition on this activity. Glutamine synthetase (GS) activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
69
2
2

Year Published

1986
1986
2016
2016

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 116 publications
(80 citation statements)
references
References 27 publications
7
69
2
2
Order By: Relevance
“…Thomas, unpublished). Further, Smith et al (1985) showed that AM fungi are able to assimilate NH % + via glutamine synthetase. The NH % + is adsorbed onto soil particles and is relatively non-mobile, so that even in moist soils depletion zones develop readily and, as with P, diffusion rather than absorption limits the rate of uptake.…”
Section: mentioning
confidence: 99%
“…Thomas, unpublished). Further, Smith et al (1985) showed that AM fungi are able to assimilate NH % + via glutamine synthetase. The NH % + is adsorbed onto soil particles and is relatively non-mobile, so that even in moist soils depletion zones develop readily and, as with P, diffusion rather than absorption limits the rate of uptake.…”
Section: mentioning
confidence: 99%
“…There were clear interactions between phosphate nutrition and enzyme activity. In general, activities of nitrate reductase and of glutamine synthetase were higher in both roots and shoots of P-sufficient plants, regardless of whether the improved P status was brought about by mycorrhizal infection or by fertilization with P. In addition, mycorrhizas have a direct effect on the glutamine synthetase activity of infected roots and glutamine synthetase has been shown to be active in fungal tissue separated from the roots (see Smith et al, 1985). This means that assimilation of ammonium as well as translocation of N compounds could occur in the fungal component of a mycorrhiza and could contribute to a mechanism of ammonium uptake similar to that envisaged for P. Nevertheless, as Ames et al (1984) emphasize, data based on total plant N, on tissue N concentrations and on percentage usage of N fertilizer failed to show that VA mycorrhizal infection increased the rate of uptake of N by plants.…”
Section: Introductionmentioning
confidence: 99%
“…Until now, considering the fact that the AM fungi are strict symbionts with very limited growth without the host roots, the origin of additional polypeptides in iVM roots was very uncertain. Approaches have been developed to study fungal polypeptides corresponding to the symbiotic stage of the AM fungi by using enzymatic digestion of host root (Capaccio & Callow, 1982;GianinazziPearson & Gianinazzi, 1983;Smith et al, 1985;Smith & Gianinazzi-Pearson, 1987;McGee & Smith, 1990;Simoneau et al, 1994). However, this strategy could lead to artefactual alterations in polypeptides of AM fungi (Smith and GianinazziPearson, 1987;McGee & Smith, 1990).…”
Section: Up and Down Regulation Of Preexisting Polypeptidesmentioning
confidence: 99%